Chaetomitrium Laevifolium - Monica Suleiman; Hiroyuki Akiyama (2014)
(1) Plants are densely branched; (2) branches are slightly flattened; (3) branch leaves are deeply concave, oblong-obovate, shortly acute and strongly constricted below apices; (4) leaf margins undulate, widely incurved in upper half, denticulate near apices, serrate from shoulder to mid-leaf, denticulate below, with simple teeth; (5) costae are strong; (6) lamina cells are incrassate, smooth or only slightly prorulate, and becoming smaller towards the apices; (7) setae are 7 mm long, setulose half above and papillose below; (8) capsules are inclined, cylindrical, slightly rough; (9) calyptrae large, with long cilia at the base.